2018
DOI: 10.1063/1.5040852
|View full text |Cite
|
Sign up to set email alerts
|

The validity of the potential model in predicting the structural, dynamical, thermodynamic properties of the unary and binary mixture of water-alcohol: Ethanol-water case

Abstract: Thermodynamic, dynamical, and structural properties of ethanol are numerically studied using two ethanol models: TraPPE-UA and OPLS-AA. These properties are computed with temperatures ranging from 200K to 300K, with steps of 10K, and also with different mole fractions of ethanol at 300K. The TraPPE-UA and OPLS-AA models are mixed with two water models: SPCE and TIP4P. These models have been previously shown to be the best models of methanol among nine different models. In our previous paper on methanol-water m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…We note that these force fields allow for flexibility of the ethanol and water molecular structures during the course of the simulations. Several recent molecular dynamics studies have shown how such force fields provide a reliable description of the structure of ethanol–water mixtures, with excellent reproduction of the experimental radial distribution functions in most cases. To have a statistically significant sample in the extreme regions of the concentration range, i.e., where the content of water or ethanol is particularly low, the volume of the slab representing the system must be particularly large and, at the same time, must have a transversal dimension adequate to be able to distinguish a surface region from a bulk region.…”
Section: Surface Properties Of Ethanol Aqueous Solutionsmentioning
confidence: 99%
“…We note that these force fields allow for flexibility of the ethanol and water molecular structures during the course of the simulations. Several recent molecular dynamics studies have shown how such force fields provide a reliable description of the structure of ethanol–water mixtures, with excellent reproduction of the experimental radial distribution functions in most cases. To have a statistically significant sample in the extreme regions of the concentration range, i.e., where the content of water or ethanol is particularly low, the volume of the slab representing the system must be particularly large and, at the same time, must have a transversal dimension adequate to be able to distinguish a surface region from a bulk region.…”
Section: Surface Properties Of Ethanol Aqueous Solutionsmentioning
confidence: 99%
“…The simulation results that are presented here have been obtained by using a classical nonpolarizable model interaction potential for neat ethanol (TraPPE-UA) and neat water (SPC/E) These model interaction potentials are known to successfully predict a number of neat liquid properties measured under ambient conditions. The TraPPE-UA interaction parameters were found to successfully predict the temperature-dependent experimental diffusivities, composition-dependent surface tension, dielectric relaxation properties, and static structure factors of aqueous solutions of alcohol. In addition, the experimental azeotropic conditions for ethanol-hexane and ethanol-benzene binary mixtures were successfully predicted by the TraPPE-UA potential . All these provide confidence that these model potentials for neat systems may also be employed to generate, at least, a qualitatively correct understanding of the composition-dependent structural and dynamical properties of ethanol–water binary mixtures at different temperatures.…”
Section: Computational Methods and Experimental Detailsmentioning
confidence: 70%
“…In this study, we chose the best two potential models based on their success in our previous works; [62][63][64] the Optimized Potentials for Liquid Simulations all-atoms (OPLSAA) 66 and Transferable Potentials for Phase Equilibria unite-atom (TraPPE-UA) 67 force elds. The number of interaction sites in a TraPPE-UA force eld is designed to be as small as possible without losing excessive accuracy.…”
Section: Potential Modelsmentioning
confidence: 99%
“…In our previous work, 62–65 we studied the properties of pure 1-alkanol and its mixtures with water using various models, most notably the OPLS-AA 66 and TraPPE-UA 67 models. These models demonstrated good efficiency in predicting different physical properties when compared to experimental values.…”
Section: Introductionmentioning
confidence: 99%